DOI: 10.22215/etd/2015-11076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating trivalent chromium (CRIII) toxicity on wild terrestrial plants

Abstract: Elevated chromium levels in soil from mining can impact the environment, including plants. Extensive chromite-ore deposits have been discovered in the Ring of Fire region, thus mining may increase. Chromium toxicity on wild plants is poorly understood. Concentration-response experiments were conducted to evaluate the effects of chromium on terrestrial plants. Using artificial soil, seeds of 32 species were exposed to chromium (CrIII) at concentrations (0-1000 mg/kg) simulating contamination levels.Many plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Generally, metals cannot be easily extracted from soil media in great quantities because they form complex bonds with ligands in the soil. Recent studies have shown that plants used for remediation accumulate larger amounts of heavy metals in their roots and then transfer them to aboveground biomass (Wei et al, 2011;Saleem et al, 2015;Lukina et al, 2016). This suggests that plants with greater biomass, such as mustard, rapeseed, maize and sunflower plants, can be beneficial in the field and can survive in the presence of toxic heavy metals (Cekic et al, 2017;Rizwan et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, metals cannot be easily extracted from soil media in great quantities because they form complex bonds with ligands in the soil. Recent studies have shown that plants used for remediation accumulate larger amounts of heavy metals in their roots and then transfer them to aboveground biomass (Wei et al, 2011;Saleem et al, 2015;Lukina et al, 2016). This suggests that plants with greater biomass, such as mustard, rapeseed, maize and sunflower plants, can be beneficial in the field and can survive in the presence of toxic heavy metals (Cekic et al, 2017;Rizwan et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%